The effect of Ebola virus disease on maternal health service utilisation and perinatal outcomes in West Africa: a systematic review - Zemenu Yohannes Kassa; Vanessa Scarf; Deborah Fox (BMC, 2022)
Plain Language Summary Ebola virus disease (EVD) is a serious public health concern affecting the health of humans and other primates. These outbreaks disrupt the already fragile maternal health services in West Africa. There is limited data on the effect of EVD on maternal health service utilisation and perinatal outcomes in West Africa. This systematic review aims to synthesise evidence on maternal health service utilisation and perinatal outcomes before EVD, during EVD and post EVD. This systematic review was conducted in West Africa, and the databases used were Medline, PubMed, CINAHL, Scopus, EMBASE and African journals online. Twelve studies met the inclusion criteria and were used for this systematic review synthesis. The results showed that antenatal care significantly decreased during the Ebola virus outbreak and strove to recover post-Ebola virus disease. This finding indicated that women were less likely to have an institutional birth during EVD and struggled to recover post-Ebola virus disease. Based on this finding, responsible bodies and stakeholders need to prepare locally tailored interventions to increase the number of women attending ANC, institutional childbirth, and PNC services post-EVD and future outbreaks.